Factors Associated With Preeclampsia: A Systematic Review - Hotmauli BR. Sitanggang; Asroh Yuliana; Wellina BR. Sebayang (Jurnal EduHealth, 2025)
Preeclampsia remains a significant public health threat in developed and developing countries, contributing to maternal and perinatal morbidity and mortality globally. The prevalence of preeclampsia in developed countries is 1.3% - 6%, while in other developing countries it is 1.8% - 18%. Preeclampsia is a pregnancy complication characterized by an increase in blood pressure (hypertension) that usually appears after 20 weeks of gestation, accompanied by damage to organs such as the kidneys, which can be seen from the presence of protein in the urine (proteinuria). The goal is to find out what are the factors that cause preeclampsia in mothers. This study uses the Systematic Review method in accordance with the PRISMA Guidelines. The focus of the review is determined by keywords, inclusion and exclusion criteria, article search strategies with relevant databases (PubMed, Scince Direct, and Wiley), the article selection process is described in the PRISMA flowchart, Critical Appraisal using CEBM, then data extraction, and presenting the results. There are 106 articles that are removed duplicates which are then selected from titles, abstra to full text. Finally, 11 selected articles that met the inclusion criteria, Nine themes were found in this study, namely Demographic factors, Obstetric History, Health Conditions, Family Health History, ANC Visits, PAPP-P and  β hCG, P53 Gene Changes, Based on Sex, Nonproteinuric and Placenta Location. In this review, an article related to the factors that cause preeclampsia in mothers was obtained, so it is recommended that researchers conduct further research related to preeclampsia management based on the causative factors. This is so that the problem of preeclampsia in mothers can be solved.